Effect of potassium chloride on the solvation behavior of caffeine, theophylline and theobromine: Volumetric, viscometric, calorimetry and spectroscopic approach. (15th November 2018) - Beri, Aashima; Banipal, Parampaul K.; Banipal, Tarlok S.
Highlights: Positive Δtr V 2, ϕ 0 and Δtr K s, 2, ϕ 0 may suggest the dominance of hydrophilic-ionic interactions. Bitterness of methylxanthines increase in the presence of KCl(aq.) . The d B /d T values indicate structure-breaking behavior. Exothermicity postulate the dominance of hydrophilic-ionic interactions. Abstract: The density ( ρ ), speed of sound ( u ), viscosity ( η ) and enthalpy of dilution ( q ) measurements for methylxanthines (caffeine, theophylline and theobromine) in aqueous medium and in aqueous solutions of (0.10–1.00) mol·kg −1 KCl covering a temperature range T  = (288.15–318.15) K and at p  = 101.325 kPa have been accomplished using a density and sound velocity meter, Micro-Ubbelohde type capillary viscometer and Isothermal Titration Calorimetry, respectively. Transfer parameters evaluated from the data suggest that competition among various interactions exists at low and high molalities of KCl(aq.) solutions. The increase in bitterness and decrease in hydration number of methylxanthines with the m B values have been observed. The dehydration effect of KCl(aq.) at low molalities on the methylxanthines has also been established using ITC. Positive change in the chemical shifts ( 1 H NMR) and increase in absorption intensity (UV–vis) of methylxanthines in the presence of KCl(aq.) further support our results.